The digital native : myth and reality - Neil Selwyn (New information perspective, 2009)
Purpose – The purpose of this paper is to develop and promote a realistic understanding of young people and digital technology with a view to supporting information professionals in playing useful and meaningful roles in supporting current generations of young people. In particular the paper aims to offer a critical perspective on popular and political understandings of young people and digital technologies – characterised by notions of “digital natives”, the “net generation” and other commonsense portrayals of expert young technology users. The paper seeks to consider the accuracy of such descriptions in reflecting young people’s actual uses of digital technology and digital information. Design/methodology/approach – The paper provides a comprehensive review of the recent published literatures on young people and digital technology in information sciences, education studies and media/communication studies. Findings – The findings show that young people’s engagements with digital technologies are varied and often unspectacular – in stark contrast to popular portrayals of the digital native. As such, the paper highlights a misplaced technological and biological determinism that underpins current portrayals of children, young people and digital technology. Originality/value – The paper challenges the popular assumption that current generations of children and young people are innate, talented users of digital technologies. Having presented a more realistic basis for approaching generational differences in technology use, the paper explores the functions and roles that information professionals can be expected to play in supporting young people in the digital age.   Keywords Children (age groups), Youth, Internet, Digital communication systems
Keywords: jeunesse; lecture numérique